2018
DOI: 10.14814/phy2.13575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate-induced increases in human muscle power: high versus low responders

Abstract: Maximal neuromuscular power is an important determinant of athletic performance and also quality of life, independence, and perhaps even mortality in patient populations. We have shown that dietary nitrate (NO 3 −), a source of nitric oxide (NO), improves muscle power in some, but not all, subjects. The present investigation was designed to identify factors contributing to this interindividual variability. Healthy men (n = 13) and women (n = 7) 22–79 year of age and weighing 52.1–114.9 kg were studied using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
73
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 38 publications
(94 reference statements)
13
73
4
1
Order By: Relevance
“…The purpose of the present study was to test the hypothesis that acute dietary NO3supplementation would improve muscle speed and power in healthy older men and women. In keeping with our previous studies (21)(22)(23)(24), we found that acute NO3ingestion increased Vmax and Pmax in older subjects by ~11 and ~4%, respectively. Although modest in size, the potential clinical significance of these changes is tremendous.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The purpose of the present study was to test the hypothesis that acute dietary NO3supplementation would improve muscle speed and power in healthy older men and women. In keeping with our previous studies (21)(22)(23)(24), we found that acute NO3ingestion increased Vmax and Pmax in older subjects by ~11 and ~4%, respectively. Although modest in size, the potential clinical significance of these changes is tremendous.…”
Section: Discussionsupporting
confidence: 93%
“…Their baseline breath NO levels, for example, were comparable to those we have found previously in younger subjects (21,22). Their baseline plasma NO3and NO2concentrations were also similar to those we have measured previously (22).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations